Alvin Ho : allergic to girls, school, and other scary things - Look, Lenore; Pham, LeUyen (New York : Schwartz & Wade Books, 2008)
A young boy in Concord, Massachusetts, who loves superheroes and comes from a long line of brave Chinese farmer-warriors, wants to make friends, but first he must overcome his fear of everything.
006-010.
600
Accelerated Reader/Renaissance Learning
Keywords: Fear -- Fiction; Self-confidence -- Fiction; Friendship -- Fiction; Chinese Americans -- Fiction; Concord (Mass.) -- Fiction